2018
DOI: 10.4103/ijp.ijp_737_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Portulaca oleracea and α-linolenic acid on oxidant/antioxidant biomarkers of human peripheral blood mononuclear cells

Abstract: OBJECTIVES:Various pharmacological effects including antioxidant property of Portulaca oleracea L. were reported previously. In the present study, the effect of the extract of the plant and its constituent, α-linolenic acid (ALA), on oxidant and antioxidant markers of PHA/non-stimulated human mononuclear cells was evaluated.MATERIALS AND METHODS:The effect of 10, 40, and 160 μg/ml of P. oleracea and 5, 15, and 45 μg/ml of ALA or dexamethasone (0.1 mM) on nitric oxide (NO), malondialdehyde (MDA), total thiol (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Moreover, PO extract notably ameliorated the oxidative stress induced by streptozotocin in the testicular tissue of rats. This is in line with previous works that demonstrated the anti-oxidative properties of PO in both male [55,56] and female rodents [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, PO extract notably ameliorated the oxidative stress induced by streptozotocin in the testicular tissue of rats. This is in line with previous works that demonstrated the anti-oxidative properties of PO in both male [55,56] and female rodents [57,58].…”
Section: Discussionsupporting
confidence: 93%
“…Antioxidants are very important for human health as they reduce risk of cell damage by free radicals [ 7 ]. Several studies have investigated and proved the antioxidant potential of purslane [ 27 , 30 , 142 , 176 ]. Several compounds have been isolated from purslane and their antioxidant activities have been proved.…”
Section: Ethnopharmacological Potential Of Purslanementioning
confidence: 99%
“…Recent advancements in the quantitative tools for the analysis of phytochemicals has led to the identification of several hundred metabolites from various parts of the purslane [ 5 , 7 , 10 , 18 , 21 , 22 ]. Using ethnobotanical leads, scientists have tested the efficacy of purslane as a medicinal plant using in vitro as well as in vivo studies and have found impressive results on its pharmacological potential [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The confirmation of the medicinal uses against the diseases using modern scientific studies provide evidence in support of the ethno medicinal properties of the purslane.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are very important for human health as they reduce risk of cell damage by free radicals (Korade and Deokule, 2015). Several studies have investigated and proved ant-oxidant potential of Purslane (Alam et al, 2014;Baradaran-Rahimi et al, 2019;Yahyazadeh Mashhadi et al, 2018). Several compounds have been isolated from Purslane and their antioxidant activities have been proved.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…Recent advancements in the quantitative tools for the analysis of phytochemicals has led to the identi cation of several hundred metabolites from various parts of the Purslane (Mohamed and Hussein, 1994;Uddin et al, 2014;Okafor and Ezejindu, 2014;Negi, 2018). Using ethnobotanical leads, scientists have tested the e cacy of Purslane as medicinal plant using in vitro as well as in vivo studies and found impressive results (Huang and Dong, 2011;Wang and Yang, 2010;Al-Sheddi et al, 2015;Bai et al, 2016;Yahyazadeh Mashhadi et al, 2018;Baradaran-Rahimi et al, 2019;Roozi, et al, 2019). The con rmation of the medicinal uses against the diseases using modern scienti c studies provide evidence in support of the ethno medicinal properties of the Purslane.…”
Section: Introductionmentioning
confidence: 99%